1990
DOI: 10.1182/blood.v75.2.428.bloodjournal752428
|View full text |Cite
|
Sign up to set email alerts
|

High human T-cell lymphotropic virus type I proviral DNA load with polyclonal integration in peripheral blood mononuclear cells of French West Indian, Guianese, and African patients with tropical spastic paraparesis

Abstract: Human T-cell lymphotropic virus type I (HTLV-I) proviral integration status was examined by Southern blot analysis in peripheral blood mononuclear cell (PBMC) DNA from patients presenting a tropical spastic paraparesis (TSP) and serological evidence of HTLV-I infection. Surface phenotype and morphological aspects of PBMC were also studied. A polyclonal HTLV-I proviral integration was found in the PBMC of the 10 patients studied irrespective of their geographical origin (French West Indies, French Guiana, and A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
33
1
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 4 publications
3
33
1
2
Order By: Relevance
“…A second is suggested by reports that heat-inactivated HTLV-1 virions themselves have mitogenic properties in some circumstances (7). A striking aspect of HTLV-1 infection to emerge from this work, also reported by Gessain and colleagues (11), is the high provirus load in peripheral blood. Southern blot analysis of genomic DNA prepared from whole peripheral blood suggested that approximately 10% of all leukocytes carry an HTLV-1 provirus in subjects with TSP, assuming that infected cells contain a single provirus (39).…”
Section: Bpsupporting
confidence: 79%
“…A second is suggested by reports that heat-inactivated HTLV-1 virions themselves have mitogenic properties in some circumstances (7). A striking aspect of HTLV-1 infection to emerge from this work, also reported by Gessain and colleagues (11), is the high provirus load in peripheral blood. Southern blot analysis of genomic DNA prepared from whole peripheral blood suggested that approximately 10% of all leukocytes carry an HTLV-1 provirus in subjects with TSP, assuming that infected cells contain a single provirus (39).…”
Section: Bpsupporting
confidence: 79%
“…Human T-cell leukemia virus type I (HTLV-I) is associated with adult T-cell leukemia/lymphoma (ATL) and with tropical spastic paraparesis/HTLV-I-associated myelopathy (TSP/HAM) (10,24,26,41,43). While the mechanisms by which HTLV-I causes TSP/HAM are unknown, a higher viral load and spontaneous proliferation of infected T-cells are observed in TSP/ HAM compared with those in ATL (11,16,27,38,44).…”
mentioning
confidence: 99%
“…Flow cytometric analysis (kindly performed by F. Valensi, Necker Hospital, Paris, France) of the cultured cell lines was performed with a series of monoclonal antibodies directed against human T-cell and B-cell antigens as previously described (30).…”
Section: Serological Tests For Serum Samples Obtained Through the Pamentioning
confidence: 99%